Modifikasi Alokasi Waktu Untuk Anak Berkebutuhan Khusus (ABK) Dalam Kurikulum Merdeka Di SMPN 40 Jakarta - Mohamad Firdaus Nasori; Desy Safitri; Sujarwo Sujarwo (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2024)
Learning organisation strategies or Learning Strategies refer to the ways used by educators or instructors to organise and structure the learning process to be effective and efficient. Where there are 3 indicators, namely modification of time allocation, modification of content or material and modification of the teaching-learning process. Sekolah Menengah Pertama Negeri 40 Jakarta opens a pathway for students with special needs or often called people with disabilities. This study aims to describe the modification of time allocation for children with special needs (ABK) in the Merdeka Curriculum of SMPN 40 Jakarta. The type of research used in this study is a descriptive method with a quantitative approach. Social Studies Learning Strategy for children with special needs is included in the good categorisation with a percentage of data accumulation results of 68%. This means that the modification of time allocation for children with disabilities at SMPN 40 Jakarta has been done well.